PERBEDAAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN DENGAN MANAJEMEN LABA TINGGI DAN MANAJEMEN LABA RENDAH (Studi Empiris Pada Perusahaan-Perusahaan Indeks LQ45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2013) - Ananda, Ode Satria; -, Zulbahridar; Lukman, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to determine whether corporate social responsibility disclosures in LQ45 company listed on Indonesia Stock Exchange (IDX) in year 2011-2013 differ between firm with high and lower earnings management. Dependent variable used in this study is corporate social responsibility disclosure that measured using CSR Index (CSRI) based on GRI. Independent variable used in this study isearning management thatmeasured using proxy of discretoinary accruals in The Khotarietal, Model (2005). The population in this study consists of LQ45 listed firm in Indonesia Stock Exchange in year 2010, 2011, and 2012. Sampling method used is purposive sampling. The total sample are 98 firm data. Data collection techniques in this research uses secondary data, that is annual report of the last year 31 december of 2011-2013, while Data analysis technique in this research is using different test analysis of independent sample test method were processed with SPSS version 21 for Windows. The result of this research indicated that there was difference of corporate social responsibility disclosures between firms with high and lower earnings management.Keywords: corporate social, responsibility, disclosure, and management